2019
DOI: 10.32098/mltj.03.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Tendon to bone healing and its implications for surgery

Abstract: Entheses are complex structures which act to reduce stress concentrations between tendon and skeleton tissues. Understanding the development and function of the enthesis organ has implications for surgical repair, particularly in regards to healing and the regulation of tendon to bone engraftment. In this paper we review the development and function of entheses as well as the enthesis organ concept. Next we examine the process of tendon to bone healing and how this can be regulated, before addressing implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…Furthermore, tendon-to-bone healing involves a third category, which relies on a combined healing model including both bone and soft tissue. 5 NSAIDs were not shown to affect soft tissue healing but did have a detrimental effect on tendon-to-bone healing in animal models. 6 NSAIDs have a direct effect on the mediators involved in tendon healing.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, tendon-to-bone healing involves a third category, which relies on a combined healing model including both bone and soft tissue. 5 NSAIDs were not shown to affect soft tissue healing but did have a detrimental effect on tendon-to-bone healing in animal models. 6 NSAIDs have a direct effect on the mediators involved in tendon healing.…”
Section: Discussionmentioning
confidence: 86%
“…Because neovascularization rarely occurs from the tuberosity bone into the reattached tendon, the nutrients and healing factors are provided to the repair site in an antegrade fashion via epitendinous blood vessels and diffusion into the synovial fluid through the circulus articuli vasculosis around the joint capsule. 2 These healing factors foster chemotaxis of fibroblasts and the proliferation of a collagen and extracellular matrix around the repair site. 21 Oguma et al showed that this collagen is then anchored to the repair interface via the formation of woven bone.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 An established bone tunnel suture fixation method of the supraspinatus was used. 2 , 14 The surgeon was blinded to group designation at the time of surgery. Daily gavages continued until sacrifice date.…”
Section: Methodsmentioning
confidence: 99%
“…There have been no studies investigating whether remnant tissue is pathological or physiological tissue that can be preserved. 23,24 The limitations of this study include the modest number of articles due to the narrow inclusion criteria, which may limit generalization to the wider population. The outcome-measurement tools were heterogeneously reported, preventing direct comparison of outcomes and undermining the need for standardized methods.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no studies investigating whether remnant tissue is pathological or physiological tissue that can be preserved. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%